Analisis Sistem Monitoring Suhu dengan Sensor LM35 Menggunakan OHP (Over Head Projector) Berbasis Raspberry Pi - Risky Via Feriyanti; Aziz Yulianto Pratama; Dwi Novianto (Journal of Applied Electrical Engineering, 2022)
Laboratory monitoring, which is usually carried out by laboratory personnel, is now carried out in real time and in a modern way. The purpose of this laboratory monitoring is to determine the room temperature using a K-type thermocouple which is standardized with a standard thermometer. The results of these objectives are to know the validation value and to know the heuristic value of the K-type thermocouple from the sensor in the K-type thermocouple called the LM35 sensor. These results are obtained from a system that has been created named room temperature monitoring in real time using a K-type thermocouple. This system was established from the use of the damaged OHP (Over Head Projector) as a mini laboratory, then around the OHP were placed four pieces of glass on all four sides that had been coated with aluminum, and then placed the LM35 sensor which was placed in the corners of the OHP side and outside the glass coated with aluminum. Then the wire from the K-type thermocouple is inserted in the middle position in the OHP. The LM35 sensor that is inserted into the OHP is connected to the Raspberry pi Type B which serves as the brain of the system that is made. This system displays the ADC value and Temperature value when the Halogen lamp is turned on in an artificial laboratory (OHP). Monitoring measurements are carried out with 1 measurement on a standard thermometer and four measurements on a test instrument (Type-K Thermocouple). The results of the sensor characterization are test accuracy values "‹"‹of 98.21%. Precision results are 99.81%. Linearity results are 99.91% and the sensor sensitivity result is 0.27.